2005
DOI: 10.1074/jbc.m412374200
|View full text |Cite
|
Sign up to set email alerts
|

Actin Cytoskeleton as the Principal Determinant of Size-dependent DNA Mobility in Cytoplasm

Abstract: The cytosol of mammalian cells is a crowded environment containing soluble proteins and a network of cytoskeletal filaments. Gene delivery by synthetic vectors involves the endocytosis of DNA-polycation complexes, escape from endosomes, and diffusion of non-complexed DNA through the cytosol to reach the nucleus. We found previously that the translational diffusion of large DNAs (>250 bp) in cytoplasm was greatly slowed compared with that of smaller DNAs (Lukacs, G. L., Haggie, P. Gene delivery by non-viral vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
157
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(167 citation statements)
references
References 39 publications
7
157
2
1
Order By: Relevance
“…Verkman and co-workers recently reported that the actin cytoskeleton is the principle determinant for passive diffusion through the cytoplasm, and that disruption of the actin cytoskeleton through the addition of either cytochalasin D or latrunculin B was sufficient in vitro to dissipate the retarding sieving effect seen in the diffusion of large macromolecules or linear DNA fragments. 32 This result echoes the earlier findings of Popov and Poo, 33 suggesting that disruption or dissipation of the actin cytoskeleton could improve cytoplasmic trafficking of macromolecules. Viruses such as SV40 take a similar approach in disrupting the actin cytoskeleton through the activation of tyrosine kinases to aid in their movement through the cytoplasm.…”
Section: The Percent Of Apoptotic Cells (7sd) Is Shownsupporting
confidence: 87%
“…Verkman and co-workers recently reported that the actin cytoskeleton is the principle determinant for passive diffusion through the cytoplasm, and that disruption of the actin cytoskeleton through the addition of either cytochalasin D or latrunculin B was sufficient in vitro to dissipate the retarding sieving effect seen in the diffusion of large macromolecules or linear DNA fragments. 32 This result echoes the earlier findings of Popov and Poo, 33 suggesting that disruption or dissipation of the actin cytoskeleton could improve cytoplasmic trafficking of macromolecules. Viruses such as SV40 take a similar approach in disrupting the actin cytoskeleton through the activation of tyrosine kinases to aid in their movement through the cytoplasm.…”
Section: The Percent Of Apoptotic Cells (7sd) Is Shownsupporting
confidence: 87%
“…The difference between P UL,1 and P UL,2 results from a fourfold reduction of the solute diffusion coefficient in cytoplasm versus saline. [56,57] Detection of an aquaporin-mediated increase in P M would require that P M of the lipid matrix is ≤10 −4 cm s −1 , that is, several orders of magnitude below the value measured with a tracer technique for planar lipid membranes. [58] In the absence of any experimental proof for this very unlikely anticipation, Xenopus oocytes may not be used for P M measurements of CO 2 .…”
Section: Gas Transport Through Membranes and Membrane Channelsmentioning
confidence: 99%
“…On the other hand, physical approaches such as microinjection [7,8] and electroporation [9] are performed to incorporate naked DNAs directly into cytoplasm across the plasma membrane. Some naked DNAs diffuse in the cytoplasm to the nucleus [10]. The diffusion of exogenous DNAs in cytoplasm is relatively slow compared with that in solution [10,11], and it is hard for large DNA to cross the nuclear membrane [11].…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion of exogenous DNAs in cytoplasm is relatively slow compared with that in solution [10,11], and it is hard for large DNA to cross the nuclear membrane [11]. Under such conditions in cytoplasm, the existence of nuclease degradation in cytoplasm is suggested [10][11][12][13][14][15]. It is presumed that the translocation and nuclear uptake of transfected DNA compete with degradation by cytoplasmic nucleases [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation